A sludge treating agent and preparation method thereof
By using inorganic polymer flocculants, calcium salts, carbonates, silicates, ion adsorption additives and modified flocculants in sludge treatment agents, the problems of slow settlement speed of sludge treatment agents and insufficient adsorption capacity of heavy metals are solved, efficient settlement of sludge and effective adsorption of heavy metals are achieved, and the efficiency of sludge treatment and environmentally friendly heavy metal recovery are promoted.
Patent Information
- Application Number
- CN202411540893.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-09-12
AI Technical Summary
The sedimentation rate of ordinary sludge treatment agents is average, the sludge treatment efficiency is not high, the dehydration performance needs to be improved, and the adsorption capacity of heavy metal ions is limited, which affects the ecological environment.
A sludge treatment agent including inorganic polymer flocculants, calcium salts, carbonates, silicates, ion adsorption additives and modified flocculants is adopted. Through the branched carboxyl and quaternary ammonium groups of the modified flocculants, and the tetraazane heterocyclic structure of the ion adsorption additives, the efficient sedimentation of the sludge and the effective adsorption of heavy metal ions is achieved.
It significantly improves the sedimentation rate and dehydration performance of the sludge, reduces the content of heavy metal ions in the filtrate, reduces the toxicity of the filtrate, and concentrates the heavy metal ions in the filter cake, providing feasibility for its recycling and reuse.
Smart Images

Figure CN119330552B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sludge treating agents, and specifically discloses a sludge treating agent and a preparation method thereof. Background Art
[0002] With the acceleration of industrialization and the improvement of urbanization, the discharge of sewage has increased dramatically, and a large amount of sludge has been generated. As a by-product of sewage treatment, sludge has a very complex composition. It not only contains a large amount of water, but also contains a variety of organic matter, inorganic matter, microorganisms, heavy metals and other harmful substances. How to effectively treat sludge has become an urgent part of environmental governance.
[0003] Traditional sludge treatment methods mainly include natural drying, mechanical dehydration, incineration, landfill and other methods. These methods have limitations in treatment efficiency, energy consumption, floor space and secondary pollution control. In particular, heavy metal pollution can cause water pollution if not properly handled, posing a potential threat to the ecological environment. Sludge treatment agent is a treatment agent specially used to improve the properties of sludge. It can effectively improve the dehydration performance and sedimentation rate of sludge. However, with the acceleration of urbanization, the amount of sludge discharged is huge. Ordinary sludge treatment agents have average sludge treatment efficiency, and most of them focus on improving the dehydration performance of sludge and changing the fluidity of sludge. The adsorption capacity of heavy metal ions is limited. The power is limited, therefore, people usually improve the use of sludge treatment agents. For example, the patent with announcement number CN110372175B announces a sludge conditioner and a sludge drying treatment method. This sludge treatment agent breaks the sludge wall and breaks the chain to release the microbial moisture in the sludge, solves the problem of cell-bound water that is difficult to remove in the sludge, and chelates and solidifies the free metals in the sludge through adsorption, chelation and solidification functions, so that it is converted from a heavy metal form to a stable state, reducing the biological effectiveness of heavy metals and reducing the ecological impact of heavy metals. However, cement is added as the core of cohesion in this patent, which makes the post-treatment of the solidified sludge more difficult, which is not conducive to the recovery and utilization of heavy metals. Summary of the invention
[0004] The purpose of the present invention is to provide a sludge treatment agent and a preparation method thereof, which solve the following technical problems: (1) the settling speed of ordinary sludge treatment agents is average, the sludge treatment efficiency is not high, and the dewatering performance needs to be improved; (2) the adsorption capacity of ordinary sludge treatment agents for heavy metal ions is limited, and the high heavy metal content affects the ecological environment.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A sludge treatment agent comprises the following raw materials in parts by weight: 25-50 parts of inorganic polymer flocculant, 22-30 parts of calcium salt, 3-6 parts of carbonate, 4-8 parts of silicate, 12-16 parts of ion adsorption additive, 80-100 parts of modified flocculant, and 6-8 parts of magnetic powder; the ion adsorption additive is prepared by modifying the surface of bentonite and introducing a tetranitrogen heterocyclic structure; the modified flocculant is prepared by copolymerizing acrylamide and maleic anhydride and then introducing a quaternary ammonium group.
[0007] Furthermore, the inorganic polymer flocculant is any one of polyaluminum chloride, polyaluminum sulfate, polyaluminum phosphate, polyferric sulfate, polyaluminum ferric bisphosphate, and polyferric phosphate; the calcium salt is any one of calcium chloride, calcium sulfate, calcium chlorate, calcium gluconate, and calcium perchlorate; the carbonate is any one of potassium carbonate, magnesium carbonate, calcium carbonate, sodium carbonate, and aluminum carbonate; the silicate is any one of calcium silicate, silicon dioxide, dicalcium silicate, and tricalcium silicate.
[0008] Furthermore, the preparation method of the ion adsorption additive comprises the following steps:
[0009] The bentonite is placed in cyclohexane, and after ultrasonic dispersion for 10-15 minutes, 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid is added, the temperature is raised for reaction, and after suction filtration, washing, and vacuum drying, an ion adsorption additive is obtained.
[0010] In this scheme, the carboxyl group in the structure of 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid interacts with the hydroxyl group on the surface of bentonite to obtain an ion adsorption additive with a tetraazacyclic structure coated on the surface. The ion adsorption additive has a large specific surface area and a layered structure based on bentonite, and can effectively adsorb suspended matter, colloidal particles and some soluble substances in the sludge, accelerate the sedimentation efficiency of sludge particles, reduce the moisture content in the sludge, and effectively improve the dehydration and sedimentation of the sludge. At the same time, the tetraazacyclic structure connected to the surface The four nitrogen atoms in the structure can form a coordination effect with the difficult-to-sediment heavy metal ions in the sludge. The adsorption performance of bentonite and the coordination ability of the tetranitrogen heterocyclic ring on its surface with heavy metal ions are used to make the two produce a synergistic effect. This ion adsorption additive is used as a component of the sludge treatment agent. It can effectively adsorb and settle the heavy metal ions in the sludge, greatly improve the removal rate of heavy metal ions in the sludge filtrate, reduce the damage to the environment caused by filtrate discharge, and effectively concentrate the heavy metal ions in the filter cake, providing feasibility for the recovery and reuse of heavy metal ions.
[0011] Furthermore, the temperature of the temperature-raising reaction is 75-85° C. and the time is 5-6 hours.
[0012] Furthermore, the preparation method of the modified flocculant comprises the following steps:
[0013] S1: placing acrylamide and maleic anhydride in toluene, mixing and stirring thoroughly, adding an initiator, reacting in a water bath at 70-75° C. for 3.5-5 h, discharging after cooling, using methanol aqueous solution for sedimentation treatment, filtering, washing and vacuum drying to obtain maleic anhydride polyacrylamide;
[0014] S2: Place maleic anhydride polyacrylamide in N,N-dimethylformamide, mix and stir thoroughly, introduce nitrogen, add 2,3-dihydroxypropyltrimethylammonium chloride and catalyst, heat to 90-95°C and react for 3-5h. After reaction, collect the product to obtain a modified flocculant.
[0015] In this scheme, under the action of an initiator, the allyl group in the acrylamide structure and the alkenyl group in the maleic anhydride structure undergo free radical polymerization to obtain maleic anhydride polyacrylamide, and then under the action of a catalyst, the maleic anhydride group in the maleic anhydride polyacrylamide structure and the hydroxyl group in the 2,3-dihydroxypropyltrimethylammonium chloride structure undergo a ring-opening esterification reaction to obtain a modified flocculant. The modified flocculant has a branch chain containing multiple carboxyl groups and quaternary ammonium groups. The carboxyl group can adsorb heavy metal ions in the sludge and produce a synergistic effect with the ion adsorption additive to reduce the content of heavy metal ions in the sludge filtrate and reduce the toxicity of the filtrate. The quaternary ammonium group has strong cationicity and can cause the modified flocculant to carry a positive charge in the sludge, thereby generating static electricity with the negatively charged colloidal particles. Electric attraction promotes the flocculation and sedimentation process, and the quaternary ammonium group on the side chain of the modified flocculant long chain can penetrate into the sludge better through electrostatic action, which can not only increase the contact area between the modified flocculant and the sludge, thereby exerting a better flocculation effect, but also the modified flocculant has a three-dimensional network structure. As the gaps and surface area between the polymer chains increase, its adsorption performance for sludge particles is enhanced. At the same time, due to the emergence of the network structure, the polymer chains can better stretch and entangle the sludge particles to form larger floccules, effectively changing the physical and chemical properties of the sludge and reducing its specific resistance, thereby accelerating the sedimentation and dehydration process of the sludge. By using this modified flocculant as the main component of the sludge treatment agent, the sludge treatment rate is effectively improved.
[0016] Furthermore, in step S1, the initiator is any one of azobisisobutyronitrile and azobisisoheptanenitrile.
[0017] Furthermore, in step S1, the mass fraction of the methanol aqueous solution is 50-55%.
[0018] Furthermore, in step S2, the catalyst is p-toluenesulfonic acid.
[0019] A method for preparing a sludge treating agent comprises the following preparation steps:
[0020] Step 1: Place inorganic polymer flocculant, calcium salt, carbonate, silicate, and ion adsorption additive in a mixing agitator, and stir for 15-20 minutes to obtain a mixture;
[0021] Step 2: Add the modified flocculant to the mixture and continue stirring for 15-25 minutes, then add the magnetic powder and stir thoroughly for 1-1.5 hours to obtain the sludge treating agent.
[0022] Beneficial effects of the present invention:
[0023] The present invention prepares ion adsorption additives and modified flocculants to participate in the preparation process of the sludge treatment agent, so that the prepared sludge treatment agent has excellent flocculation effect, effectively improves the sedimentation rate of the sludge, and can also reduce the heavy metal content in the sludge filtrate, reduce the toxicity of the filtrate, and concentrate the heavy metal ions in the filter cake, providing feasibility for the recovery and reuse of heavy metal ions.
[0024] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0026] Figure 1 This is a graph showing the sedimentation rates of bentonite and ion adsorption additives in a dispersant according to the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The preparation methods of the ion adsorption additives and modified flocculants in the following examples and comparative examples of the present invention are as follows:
[0029] 1. Preparation of ion adsorption additives
[0030] 5 g of bentonite was placed in 120 ml of cyclohexane, and after ultrasonic dispersion for 10 minutes, 4.5 g of 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid was added, the temperature was raised to 75°C, the reaction was carried out for 5 hours, and after filtration, washing and vacuum drying, an ion adsorption additive was obtained.
[0031] 5g of bentonite and 5g of ion adsorption additive were placed in 150ml of toluene, and then ultrasonically dispersed for 15min before a sedimentation experiment. Figure 1 It can be seen that bentonite settles very quickly in toluene and reaches sedimentation equilibrium within 4 hours; the sedimentation rate of the ion adsorption additive is slower, reaching sedimentation equilibrium within 10 hours, indicating that the ion adsorption additive has better dispersion performance in toluene. This is because bentonite is easy to agglomerate when dispersed in toluene, and the aggregation of particles causes the sedimentation rate to become faster. The surface of the ion adsorption additive is modified by the organic matter 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid, which improves its dispersibility in organic solvents, thereby slowing down the sedimentation rate.
[0032] 2. Preparation of modified flocculant
[0033] S1: 3 g acrylamide and 2.8 g maleic anhydride were placed in 60 ml toluene, mixed and stirred thoroughly, and then 1 g azobisisobutyronitrile was added. The mixture was reacted in a water bath at 70° C. for 3.5 h, cooled and discharged, and precipitated with a 50% methanol aqueous solution. The mixture was filtered, washed, and vacuum dried to obtain maleic anhydride polyacrylamide;
[0034] The content of maleic anhydride in maleic anhydride polyacrylamide was measured by titration. 1 g of maleic anhydride polyacrylamide was weighed as a sample, 60 ml of toluene was added, and the mixture was heated under reflux for 20 min and mixed thoroughly. After cooling, an excess of 0.1 mol / L KOH-ethanol standard solution was added, and the mixture was heated under reflux for 8 h. After cooling to room temperature, 1 ml of phenolphthalein indicator was added, and the excess KOH-ethanol standard solution was counter-titrated with 0.1 mol / L HCl-isopropanol standard solution. The amount of excess alkali consumed and the amount of acid neutralized were recorded. The formula is listed to calculate the content of maleic anhydride in the sample soil: Maleic anhydride content (%) = 9.806 (VC-C1V1) / 2m; where C is KOH-ethanol standard solution, mol / L; V is the volume of excess KOH-ethanol standard solution added, ml; C1 is HCl-isopropanol standard solution, mol / L; V1 is the volume of HCl-isopropanol standard solution consumed by back titration and alkali neutralization, ml; m is the mass of the sample, g; after calculation, the content of maleic anhydride in the obtained sample is 10.28%.
[0035] S2: Place 3.8 g of maleic anhydride polyacrylamide in 80 ml of N,N-dimethylformamide, mix and stir thoroughly, introduce nitrogen, add 3 g of 2,3-dihydroxypropyltrimethylammonium chloride and 0.05 g of p-toluenesulfonic acid, heat to 90°C and react for 3 h. After reaction, collect the product to obtain a modified flocculant.
[0036] The content of maleic anhydride in the modified flocculant was tested by titration, the specific method was the same as step S1, and after calculation, the content of maleic anhydride in the modified flocculant was 2.12%, and the loss was due to the reaction between the maleic anhydride group in the maleic anhydride polyacrylamide structure and the hydroxyl group in the 2,3-dihydroxypropyltrimethylammonium chloride structure. Example
[0037] Preparation of sludge treatment agent
[0038] Step 1: Place 25 parts of polyaluminium chloride, 22 parts of calcium chloride, 3 parts of potassium carbonate, 4 parts of calcium silicate and 12 parts of ion adsorption additive in a mixing agitator, and stir for 15 minutes to obtain a mixture;
[0039] Step 2: Add 80 parts of modified flocculant to the mixture and continue stirring for 15 minutes, then add 6 parts of magnetic powder and stir thoroughly for 1 hour to obtain a sludge treatment agent. Example
[0040] Preparation of sludge treatment agent
[0041] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate, 6 parts of silicon dioxide and 14 parts of ion adsorption additive in a mixing agitator, and stir for 18 minutes to obtain a mixture;
[0042] Step 2: Add 90 parts of modified flocculant to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent. Example
[0043] Preparation of sludge treatment agent
[0044] Step 1: Place 50 parts of polyaluminium phosphate, 30 parts of calcium gluconate, 6 parts of calcium carbonate, 8 parts of dicalcium silicate and 16 parts of ion adsorption additive in a mixing agitator, and stir for 20 minutes to obtain a mixture;
[0045] Step 2: add 100 parts of modified flocculant to the mixture and continue stirring for 25 minutes, then add 8 parts of magnetic powder and stir thoroughly for 1.5 hours to obtain the sludge treatment agent.
[0046] Comparative Example 1
[0047] Preparation of sludge treatment agent
[0048] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate and 6 parts of silicon dioxide in a mixing agitator and stir for 18 minutes to obtain a mixture;
[0049] Step 2: Add 90 parts of modified flocculant to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent.
[0050] Comparative Example 2
[0051] Preparation of sludge treatment agent
[0052] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate, 6 parts of silicon dioxide and 14 parts of ion adsorption additive in a mixing agitator, and stir for 18 minutes to obtain a mixture;
[0053] Step 2: Add 90 parts of polyacrylamide to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent, wherein the polyacrylamide was purchased from Jinan Shunyuan Chemical Co., Ltd.
[0054] Comparative Example 3
[0055] Preparation of sludge treatment agent
[0056] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate, 6 parts of silicon dioxide and 14 parts of bentonite in a mixing agitator, and stir for 18 minutes to obtain a mixture;
[0057] Step 2: Add 90 parts of modified flocculant to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent.
[0058] Performance Testing
[0059] The sludge treating agents prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were added as samples to the sludge to be treated, stirred at a speed of 100 r / min for 1 hour and then allowed to stand. After 30 minutes, the sludge treated with the samples was tested for the moisture content of the sludge filter cake, the sludge index, the sludge specific resistance and the heavy metal content of the filtrate; the mass ratio of the sample to the sludge to be treated was 120:10; wherein the moisture content of the sludge to be treated was 85%;
[0060] Test of moisture content of sludge filter cake: The treated sludge is filtered under reduced pressure to obtain wet filter cake. A clean petri dish is placed in an oven to dry to constant weight and then placed in a dryer. After cooling to room temperature, the mass of the empty petri dish is weighed and recorded as m (g). 100g of wet filter cake is placed in an empty petri dish and the mass is recorded as m1 (g). The petri dish containing the wet filter cake is placed in an oven and baked for 6 hours. After taking it out, it is cooled and weighed and the mass is recorded as m2 (g). The moisture content of the sludge filter cake is calculated according to the following formula: moisture content = (m1-m2) × 100% / (m1-m);
[0061] Sludge index test: Pour the treated sludge into a measuring cylinder, let it stand for 30 minutes to obtain sediment, read the volume of the precipitated sludge in the measuring cylinder, record it as V (ml); take out the dried constant weight petri dish, record the mass as M0 (g), vacuum filter the precipitated sludge, take out the filter cake and place it in a petri dish, dry it to constant weight, cool it to room temperature, record the mass as M (g), and calculate the sludge index according to the following formula: sludge index = V / (M-M0);
[0062] Test of sludge specific resistance: Weigh 100g of sludge after sample treatment and place it in a measuring cylinder. Filter it under a constant air pressure of P=0.6MPa. Record the volume of the filtrate every 10s until cracks appear in the filter cake layer. Calculate the sludge specific resistance according to the following formula: Sludge specific resistance=2PS 2 k / nm; where P is the filtration pressure (kg·m -2 ), S is the filtration area (m 2 ), k is the slope of the straight line represented by the filtration equation t / V=bV+a, t is the filtration time (s), V is the filtrate volume (m 3 ); n is the dynamic viscosity of the filtrate (kg·s·m -2 ); m is the dry solid weight retained on the filter medium per unit volume of filtrate (kg·m -3 );
[0063] Test of heavy metal ion content: Avio 220 Max atomic absorption spectrophotometer was used to perform vacuum filtration on the sludge to be treated and the sludge after sample treatment, and the heavy metal content in the filtrate was tested respectively. The heavy metal content in the filtrate of the sludge to be treated was 5769 mg / L, and the heavy metal content in the sludge filtrate after sample treatment was recorded as heavy metal content A. The specific test results are shown in the table below: The sedimentation rate slowed down.
[0064] 2. Preparation of modified flocculant
[0065] S1: 3 g acrylamide and 2.8 g maleic anhydride were placed in 60 ml toluene, mixed and stirred thoroughly, and then 1 g azobisisobutyronitrile was added. The mixture was reacted in a water bath at 70° C. for 3.5 h, cooled and discharged, and precipitated with a 50% methanol aqueous solution. The mixture was filtered, washed, and vacuum dried to obtain maleic anhydride polyacrylamide;
[0066] The content of maleic anhydride in maleic anhydride polyacrylamide was measured by titration. 1 g of maleic anhydride polyacrylamide was weighed as a sample, 60 ml of toluene was added, and the mixture was heated under reflux for 20 min and mixed thoroughly. After cooling, an excess of 0.1 mol / L KOH-ethanol standard solution was added, and the mixture was heated under reflux for 8 h. After cooling to room temperature, 1 ml of phenolphthalein indicator was added, and the excess KOH-ethanol standard solution was counter-titrated with 0.1 mol / L HCl-isopropanol standard solution. The amount of excess alkali consumed and the amount of acid neutralized were recorded. The formula is listed to calculate the content of maleic anhydride in the sample soil: Maleic anhydride content (%) = 9.806 (VC-C1V1) / 2m; where C is KOH-ethanol standard solution, mol / L; V is the volume of excess KOH-ethanol standard solution added, ml; C1 is HCl-isopropanol standard solution, mol / L; V1 is the volume of HCl-isopropanol standard solution consumed by back titration and alkali neutralization, ml; m is the mass of the sample, g; after calculation, the content of maleic anhydride in the obtained sample is 10.28%.
[0067] S2: Place 3.8 g of maleic anhydride polyacrylamide in 80 ml of N,N-dimethylformamide, mix and stir thoroughly, introduce nitrogen, add 3 g of 2,3-dihydroxypropyltrimethylammonium chloride and 0.05 g of p-toluenesulfonic acid, heat to 90°C and react for 3 h. After reaction, collect the product to obtain a modified flocculant.
[0068] The content of maleic anhydride in the modified flocculant was tested by titration, the specific method was the same as step S1, and after calculation, the content of maleic anhydride in the modified flocculant was 2.12%, and the loss was due to the reaction between the maleic anhydride group in the maleic anhydride polyacrylamide structure and the hydroxyl group in the 2,3-dihydroxypropyltrimethylammonium chloride structure. Example
[0069] Preparation of sludge treatment agent
[0070] Step 1: Place 25 parts of polyaluminium chloride, 22 parts of calcium chloride, 3 parts of potassium carbonate, 4 parts of calcium silicate and 12 parts of ion adsorption additive in a mixing agitator, and stir for 15 minutes to obtain a mixture;
[0071] Step 2: Add 80 parts of modified flocculant to the mixture and continue stirring for 15 minutes, then add 6 parts of magnetic powder and stir thoroughly for 1 hour to obtain a sludge treatment agent. Example
[0072] Preparation of sludge treatment agent
[0073] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate, 6 parts of silicon dioxide and 14 parts of ion adsorption additive in a mixing agitator, and stir for 18 minutes to obtain a mixture;
[0074] Step 2: Add 90 parts of modified flocculant to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent. Example
[0075] Preparation of sludge treatment agent
[0076] Step 1: Place 50 parts of polyaluminium phosphate, 30 parts of calcium gluconate, 6 parts of calcium carbonate, 8 parts of dicalcium silicate and 16 parts of ion adsorption additive in a mixing agitator, and stir for 20 minutes to obtain a mixture;
[0077] Step 2: add 100 parts of modified flocculant to the mixture and continue stirring for 25 minutes, then add 8 parts of magnetic powder and stir thoroughly for 1.5 hours to obtain the sludge treatment agent.
[0078] Comparative Example 1
[0079] Preparation of sludge treatment agent
[0080] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate and 6 parts of silicon dioxide in a mixing agitator and stir for 18 minutes to obtain a mixture;
[0081] Step 2: Add 90 parts of modified flocculant to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent.
[0082] Comparative Example 2
[0083] Preparation of sludge treatment agent
[0084] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate, 6 parts of silicon dioxide and 14 parts of ion adsorption additive in a mixing agitator, and stir for 18 minutes to obtain a mixture;
[0085] Step 2: Add 90 parts of polyacrylamide to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent, wherein the polyacrylamide was purchased from Jinan Shunyuan Chemical Co., Ltd.
[0086] Comparative Example 3
[0087] Preparation of sludge treatment agent
[0088] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate, 6 parts of silicon dioxide and 14 parts of bentonite in a mixing agitator, and stir for 18 minutes to obtain a mixture;
[0089] Step 2: Add 90 parts of modified flocculant to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent.
[0090] Performance Testing
[0091] The sludge treating agents prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were added as samples to the sludge to be treated, stirred at a speed of 100 r / min for 1 hour and then allowed to stand. After 30 minutes, the sludge treated with the samples was tested for the moisture content of the sludge filter cake, the sludge index, the sludge specific resistance and the heavy metal content of the filtrate; the mass ratio of the sample to the sludge to be treated was 120:10; wherein the moisture content of the sludge to be treated was 85%;
[0092] Test of moisture content of sludge filter cake: The treated sludge is filtered under reduced pressure to obtain wet filter cake. A clean petri dish is placed in an oven to dry to constant weight and then placed in a dryer. After cooling to room temperature, the mass of the empty petri dish is weighed and recorded as m (g). 100g of wet filter cake is placed in an empty petri dish and the mass is recorded as m1 (g). The petri dish containing the wet filter cake is placed in an oven and baked for 6 hours. After taking it out, it is cooled and weighed and the mass is recorded as m2 (g). The moisture content of the sludge filter cake is calculated according to the following formula: moisture content = (m1-m2) × 100% / (m1-m);
[0093] Sludge index test: Pour the treated sludge into a measuring cylinder, let it stand for 30 minutes to obtain sediment, read the volume of the precipitated sludge in the measuring cylinder, record it as V (ml); take out the dried constant weight petri dish, record the mass as M0 (g), vacuum filter the precipitated sludge, take out the filter cake and place it in a petri dish, dry it to constant weight, cool it to room temperature, record the mass as M (g), and calculate the sludge index according to the following formula: sludge index = V / (M-M0);
[0094] Test of sludge specific resistance: Weigh 100g of sludge after sample treatment and place it in a measuring cylinder. Filter it under a constant air pressure of P=0.6MPa. Record the volume of the filtrate every 10s until cracks appear in the filter cake layer. Calculate the sludge specific resistance according to the following formula: Sludge specific resistance=2PS 2 k / nm; where P is the filtration pressure (kg·m -2 ), S is the filtration area (m 2 ), k is the slope of the straight line represented by the filtration equation t / V=bV+a, t is the filtration time (s), V is the filtrate volume (m3 ); n is the dynamic viscosity of the filtrate (kg·s·m -2 ); m is the dry solid weight retained on the filter medium per unit volume of filtrate (kg·m -3 );
[0095] Test of heavy metal ion content: Avio 220 Max atomic absorption spectrophotometer was used to perform vacuum filtration on the sludge to be treated and the sludge after sample treatment, and the heavy metal content in the filtrate was tested respectively. The heavy metal content in the filtrate of the sludge to be treated was 5769 mg / L, and the heavy metal content in the sludge filtrate after sample treatment was recorded as heavy metal content A. The specific test results are shown in the table below: The sedimentation rate slowed down.
[0096] 2. Preparation of modified flocculant
[0097] S1: 3 g acrylamide and 2.8 g maleic anhydride were placed in 60 ml toluene, mixed and stirred thoroughly, and then 1 g azobisisobutyronitrile was added. The mixture was reacted in a water bath at 70° C. for 3.5 h, cooled and discharged, and precipitated with a 50% methanol aqueous solution. The mixture was filtered, washed, and vacuum dried to obtain maleic anhydride polyacrylamide;
[0098] The content of maleic anhydride in maleic anhydride polyacrylamide was measured by titration. 1 g of maleic anhydride polyacrylamide was weighed as a sample, 60 ml of toluene was added, and the mixture was heated under reflux for 20 min and mixed thoroughly. After cooling, an excess of 0.1 mol / L KOH-ethanol standard solution was added, and the mixture was heated under reflux for 8 h. After cooling to room temperature, 1 ml of phenolphthalein indicator was added, and the excess KOH-ethanol standard solution was counter-titrated with 0.1 mol / L HCl-isopropanol standard solution. The amount of excess alkali consumed and the amount of acid neutralized were recorded. The formula is listed to calculate the content of maleic anhydride in the sample soil: Maleic anhydride content (%) = 9.806 (VC-C1V1) / 2m; where C is KOH-ethanol standard solution, mol / L; V is the volume of excess KOH-ethanol standard solution added, ml; C1 is HCl-isopropanol standard solution, mol / L; V1 is the volume of HCl-isopropanol standard solution consumed by back titration and alkali neutralization, ml; m is the mass of the sample, g; after calculation, the content of maleic anhydride in the obtained sample is 10.28%.
[0099] S2: Place 3.8 g of maleic anhydride polyacrylamide in 80 ml of N,N-dimethylformamide, mix and stir thoroughly, introduce nitrogen, add 3 g of 2,3-dihydroxypropyltrimethylammonium chloride and 0.05 g of p-toluenesulfonic acid, heat to 90°C and react for 3 h. After reaction, collect the product to obtain a modified flocculant.
[0100] The content of maleic anhydride in the modified flocculant was tested by titration, the specific method was the same as step S1, and after calculation, the content of maleic anhydride in the modified flocculant was 2.12%, and the loss was due to the reaction between the maleic anhydride group in the maleic anhydride polyacrylamide structure and the hydroxyl group in the 2,3-dihydroxypropyltrimethylammonium chloride structure. Example
[0101] Preparation of sludge treatment agent
[0102] Step 1: Place 25 parts of polyaluminium chloride, 22 parts of calcium chloride, 3 parts of potassium carbonate, 4 parts of calcium silicate and 12 parts of ion adsorption additive in a mixing agitator, and stir for 15 minutes to obtain a mixture;
[0103] Step 2: Add 80 parts of modified flocculant to the mixture and continue stirring for 15 minutes, then add 6 parts of magnetic powder and stir thoroughly for 1 hour to obtain a sludge treatment agent. Example
[0104] Preparation of sludge treatment agent
[0105] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate, 6 parts of silicon dioxide and 14 parts of ion adsorption additive in a mixing agitator, and stir for 18 minutes to obtain a mixture;
[0106] Step 2: Add 90 parts of modified flocculant to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent. Example
[0107] Preparation of sludge treatment agent
[0108] Step 1: Place 50 parts of polyaluminium phosphate, 30 parts of calcium gluconate, 6 parts of calcium carbonate, 8 parts of dicalcium silicate and 16 parts of ion adsorption additive in a mixing agitator, and stir for 20 minutes to obtain a mixture;
[0109] Step 2: add 100 parts of modified flocculant to the mixture and continue stirring for 25 minutes, then add 8 parts of magnetic powder and stir thoroughly for 1.5 hours to obtain the sludge treatment agent.
[0110] Comparative Example 1
[0111] Preparation of sludge treatment agent
[0112] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate and 6 parts of silicon dioxide in a mixing agitator and stir for 18 minutes to obtain a mixture;
[0113] Step 2: Add 90 parts of modified flocculant to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent.
[0114] Comparative Example 2
[0115] Preparation of sludge treatment agent
[0116] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate, 6 parts of silicon dioxide and 14 parts of ion adsorption additive in a mixing agitator, and stir for 18 minutes to obtain a mixture;
[0117] Step 2: Add 90 parts of polyacrylamide to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent, wherein the polyacrylamide was purchased from Jinan Shunyuan Chemical Co., Ltd.
[0118] Comparative Example 3
[0119] Preparation of sludge treatment agent
[0120] Step 1: Place 40 parts of polyaluminium sulfate, 26 parts of calcium sulfate, 5 parts of magnesium carbonate, 6 parts of silicon dioxide and 14 parts of bentonite in a mixing agitator, and stir for 18 minutes to obtain a mixture;
[0121] Step 2: Add 90 parts of modified flocculant to the mixture and continue stirring for 20 minutes, then add 7 parts of magnetic powder and stir thoroughly for 1.2 hours to obtain a sludge treatment agent.
[0122] Performance Testing
[0123] The sludge treating agents prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were added as samples to the sludge to be treated, stirred at a speed of 100 r / min for 1 hour and then allowed to stand. After 30 minutes, the sludge treated with the samples was tested for the moisture content of the sludge filter cake, the sludge index, the sludge specific resistance and the heavy metal content of the filtrate; the mass ratio of the sample to the sludge to be treated was 120:10; wherein the moisture content of the sludge to be treated was 85%;
[0124] Test of moisture content of sludge filter cake: The treated sludge is filtered under reduced pressure to obtain wet filter cake. A clean petri dish is placed in an oven to dry to constant weight and then placed in a dryer. After cooling to room temperature, the mass of the empty petri dish is weighed and recorded as m (g). 100g of wet filter cake is placed in an empty petri dish and the mass is recorded as m1 (g). The petri dish containing the wet filter cake is placed in an oven and baked for 6 hours. After taking it out, it is cooled and weighed and the mass is recorded as m2 (g). The moisture content of the sludge filter cake is calculated according to the following formula: moisture content = (m1-m2) × 100% / (m1-m);
[0125] Sludge index test: Pour the treated sludge into a measuring cylinder, let it stand for 30 minutes to obtain sediment, read the volume of the precipitated sludge in the measuring cylinder, record it as V (ml); take out the dried constant weight petri dish, record the mass as M0 (g), vacuum filter the precipitated sludge, take out the filter cake and place it in a petri dish, dry it to constant weight, cool it to room temperature, record the mass as M (g), and calculate the sludge index according to the following formula: sludge index = V / (M-M0);
[0126] Test of sludge specific resistance: Weigh 100g of sludge after sample treatment and place it in a measuring cylinder. Filter it under a constant air pressure of P=0.6MPa. Record the volume of the filtrate every 10s until cracks appear in the filter cake layer. Calculate the sludge specific resistance according to the following formula: Sludge specific resistance=2PS 2 k / nm; where P is the filtration pressure (kg·m -2 ), S is the filtration area (m 2 ), k is the slope of the straight line represented by the filtration equation t / V=bV+a, t is the filtration time (s), V is the filtrate volume (m 3 ); n is the dynamic viscosity of the filtrate (kg·s·m -2 ); m is the dry solid weight retained on the filter medium per unit volume of filtrate (kg·m -3 );
[0127] Test of heavy metal ion content: Avio 220 Max atomic absorption spectrophotometer was used to perform vacuum filtration on the sludge to be treated and the sludge after sample treatment, and the heavy metal content in the filtrate was tested respectively. The heavy metal content in the sludge filtrate to be treated was 5769 mg / L, and the heavy metal content in the sludge filtrate after sample treatment was recorded as heavy metal content A. The specific test results are shown in the table below:
[0128]
[0129] As can be seen from the above table, the samples prepared in Examples 1 to 3 all have excellent treatment effects on sludge, and the moisture content, sludge index and sludge specific resistance of the treated sludge are all at a low level, indicating that the samples have excellent dehydration effect and excellent coagulation and sedimentation performance. After the treated sludge is filtered under reduced pressure, the content of heavy metal ions in the filtrate is greatly reduced, which is conducive to the discharge of the filtrate, and the heavy metals in the filter cake are increased, which can be more effectively recycled and utilized, and the rationalization of resource utilization is achieved. In the sample prepared in Comparative Example 1, no ion adsorption additive was added, and the treatment capacity of heavy metal ions in the sludge was limited. In the sample prepared in Comparative Example 2, no modified flocculant was added, and polyacrylamide was directly added. The dehydration effect and coagulation and sedimentation performance were not as good as those in the embodiment. In the sample prepared in Comparative Example 3, no ion adsorption additive was added, and bentonite with adsorption effect was directly added. It can be seen that although it has a certain adsorption capacity for heavy metal ions in the filtrate, the effect is not as good as that in the embodiment, because there is no grafting of tetraazacyclic structure on the surface of bentonite.
[0130] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0131] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A sludge treating agent, characterized in that: The invention comprises the following raw materials in parts by weight: 25-50 parts of inorganic polymer flocculant, 22-30 parts of calcium salt, 3-6 parts of carbonate, 4-8 parts of silicate, 12-16 parts of ion adsorption additive, 80-100 parts of modified flocculant, and 6-8 parts of magnetic powder; the ion adsorption additive is prepared by modifying the surface of bentonite and introducing a tetranitrogen heterocyclic structure; the modified flocculant is prepared by copolymerizing acrylamide and maleic anhydride and then introducing a quaternary ammonium group; The preparation method of the modified flocculant is as follows: S1: placing acrylamide and maleic anhydride in toluene, mixing and stirring thoroughly, adding an initiator, reacting in a water bath at 70-75° C. for 3.5-5 h, discharging after cooling, using methanol aqueous solution for sedimentation treatment, filtering, washing and vacuum drying to obtain maleic anhydride polyacrylamide; S2: maleic anhydride polyacrylamide is placed in N,N-dimethylformamide, after being fully mixed and stirred, nitrogen is introduced, 2,3-dihydroxypropyltrimethylammonium chloride and a catalyst are added, the temperature is raised to 90-95°C for reaction for 3-5h, and the product is collected after the reaction to obtain a modified flocculant; The preparation method of the ion adsorption additive comprises the following steps: The bentonite is placed in cyclohexane, and after ultrasonic dispersion for 10-15 minutes, 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid is added, the temperature is raised for reaction, and after suction filtration, washing, and vacuum drying, an ion adsorption additive is obtained; The initiator is any one of azobisisobutyronitrile and azobisisoheptanenitrile; The inorganic polymer flocculant is any one of polyaluminium chloride, polyaluminium sulfate, polyaluminium phosphate, polyferric sulfate, polyaluminium ferric bisphosphate and polyferric phosphate; the calcium salt is any one of calcium chloride, calcium sulfate, calcium chlorate, calcium gluconate and calcium perchlorate; the carbonate is any one of potassium carbonate, magnesium carbonate, calcium carbonate, sodium carbonate and aluminium carbonate; the silicate is any one of calcium silicate, silicon dioxide, dicalcium silicate and tricalcium silicate; In step S1, the mass fraction of the methanol aqueous solution is 50-55%; In step S2, the catalyst is p-toluenesulfonic acid.
2. A sludge treating agent according to claim 1, characterized in that: The temperature of the temperature-raising reaction is 75-85° C. and the time is 5-6 hours.
3. A method for preparing a sludge treating agent as claimed in claim 1, characterized in that: The method comprises the following preparation steps: Step 1: Place inorganic polymer flocculant, calcium salt, carbonate, silicate, and ion adsorption additive in a mixing agitator, and stir for 15-20 minutes to obtain a mixture; Step 2: Add the modified flocculant to the mixture and continue stirring for 15-25 minutes, then add the magnetic powder and stir thoroughly for 1-1.5 hours to obtain the sludge treating agent.
Citation Information
Patent Citations
A sludge conditioner and a sludge drying treatment method
CN110372175B
Method for synthesizing composite material of organic - inorganic bentonite
CN101003374A
Preparation method and application of acrylamide modified grafted corn cob
CN102250293A